Individual Creativity and Career Choices of Pre-teens in the Context of a Math-Art Learning Event - Salmi Hannu; Thuneberg Helena; Bogner Franz X.; Fenyvesi Kristof (De Gruyter, 2021)
A sample of 392 students (aged 12-13 years, M± SD: 12. 52% girls) completed a learning module integrating informal hands-on mathematics and arts activity (extending STEM to STEAM). Within a 140 minute workshop period participants worked with commercially available '4Dframe' Math and STEAM learning toolkits to design and create original, personal and individual geometrical structures. Two science pedagogues acted as tutors supervising the process and intervened only when needed. A pre-/post-test design monitored individual creativity, relative autonomy, and career choice preference. Path analysis elaborated the role of creativity (measured with two subscales: act and flow), and it showed that post-act, post-flow as well as relative autonomy are valuable predictors of career choices. Similarly, pre-creativity scores were shown to significantly predict the related post-scores: act and flow. As a consequence, our STEAM module was shown to trigger both the creativity level and the career choice preferences. Conclusions for appropriate educational settings to foster STEAM environments are discussed.